Kepastian Hukum Dalam Kemudahan Berusaha di Era Revolusi Industri 4.0 Terkait Dengan Profesi Notaris - Muhammad Akbar (Penelitian dan Pengembangan Ilmu, 2024)
The start of the Industrial Revolution 4.0 brought many changes to the world. This is an era in which the practice of automation and data exchange, as well as the use of internet technology, cloud computing, and cognitive computing will color various sectors of human life, including the realm of the profession. All changes inevitably bring two things: challenges and opportunities. Obstacles that have been found due to changes that have occurred through the Industrial Revolution 4.0 for the notary profession, notaries must always be updated about laws and regulations, and understand technology and can take advantage of digital technology to make authentic certificates. The research method in this writing is normative juridical by analyzing legal materials in the form of Law Number 2 of 2014 concerning the Position of Notary through literature study. For a notary, it is time to see the impact of the Industrial Revolution 4.0 as a challenge and opportunity for the sustainability of the notary profession